Booker's place [videorecording (DVD)] : a Mississippi story - DeFelitta, Raymond; De Felitta, Frank; Johnson, Yvette; Jones, Leroy; Jordan, David; Winter, William F.; Carter, Hodding (Tribeca Film : Distributed by New Video, 2012)
In 1966 Frank De Felitta made a documentary for NBC News about life for Southerners in Mississippi. The content of the film upset many white Southerners and led to the beating of a black man, Booker Wright, the loss of his job, and eventually his murder. Forty-six years later Booker's granddaughter, Yvette Johnson, and Frank's son, director Raymond DeFelitta, are on a quest to discover who Booker was and how he changed life for black people.